First-Line Helicobacter pylori Eradication with Vonoprazan, Clarithromycin, and Metronidazole in Patients Allergic to Penicillin - Soichiro Sue; Nobumi Suzuki; Wataru Shibata; Tomohiko Sasaki; Hiroaki Yamada; Hiroaki Kaneko; Toshihide Tamura; Tomohiro Ishii; Masaaki Kondo; Shin Maeda (Gastroenterology Research and Practice)
Aim. To assess the efficacy of 7-day first-line Helicobacter pylori eradication with vonoprazan (VPZ), clarithromycin (CAM), and metronidazole (MNZ) in patients with penicillin allergy. Methods. Patients with penicillin allergy, diagnosed with Helicobacter pylori infection and did not have history of Helicobacter pylori eradication, were eligible for the study. Twenty patients were prospectively treated with 20 mg VPZ twice daily, 200 or 400 mg CAM twice daily, and 250 mg MNZ twice daily for 7 days. We also collected the data from 30 patients retrospectively treated with proton pump inhibitor (PPI), CAM, and MNZ. Safety was evaluated in patients completing an adverse effect questionnaire. Results. Both the intention-to-treat and per-protocol effectiveness of VPZ-based eradication were 100% (95% CI: 86.1–100%; n=20). The eradication rates of PPI-based regimen were 83.3% (95% CI: 65.3–94.4%) in the ITT and 82.7% (95% CI: 64.2–94.2%) in the PP analyses. Abdominal fullness was more frequent in VCM compared to PCM. However, all patients with VCM regimen had taken 100% of their course of medication. Conclusion. Triple therapy with VPZ, CAM, and MNZ is well tolerated and effective for eradicating Helicobacter pylori in patients allergic to penicillin. This study was registered in the UMIN Clinical Trials Registry as UMIN000016335.